Effect of high intensity interval training on 8-oxoguanine DNA glycosylase and 8-hydroxy-2'-deoxyguanosine contents in the brain and liver of rats - Ehsan Afroozi-Gerow, Mohammad Esmaiel Afzalpour, Hossein TaheriChadorneshin, Seyed Hosein Abtahi-Eivary (Journal of Applied Pharmaceutical Science, 2016)
Production of reactive oxygen species (ROS) yields serious damage oxidation of proteins, lipids and genomic structures. Studies have shown that production of ROS increases during intensive exercise training. This study aimed to investigate the effect of high intensity interval training on 8-oxoguanine DNA glycosylase (OGG1) and 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels in the brain and liver of rats. 16 adult Albino Wistar rats were randomly divided into sedentary control and high intensity interval training groups. Animals ran on treadmill for 6 weeks, 6 days per week, at 95 to 100 percent of maximal oxygen consumption. Using commercial kits, the content of OGG1 and 8-OHdG were measured using sandwich ELISA assay. Data analyzed using Student’s T-test at P≤0.05 level. High intensity interval training resulted in significant increases in contents of OGG1 in brain (t14=7.22, P=0.001) and liver (t14=2.55, P=0.02) of rats. However, high intensity interval training had no significant influence on 8-OHdG levels in brain (t14=1.60, P=0.13) and liver (t14=1.28, P=0.22) of rats. Also, there were no significant differences between changes in the brain and liver contents of OGG1 (t14=0.97, P=0.34) and 8-OHdG (t14=0.42, P=0.68) of rats following high intensity interval training. Taken together, separation of the training sessions to various bouts of exercise with maximum effort, through increase in OGG1 contents, will lead to modify of 8-OHdG levels in brain and liver.